Associations between urinary glyphosate and arthritis: an US NHANES analysis - He, Xiaoyao; Mi, Liangyu; Zhao, Miaomiao; Ji, Yuli; Hu, Yuting; Gao, Yanan; Qiu, Lixia; Xu, Ke (Frontiers in Public Health, 2025)
ObjectiveAs the relationship between urine glyphosate and arthritis in adults in general is still unclear, the study set out to investigate it.MethodsA total of 1,689 people volunteered in the National Health and Nutrition Examination Surveys (US NHANES). Utilizing a multivariate logistic regression model to explore the association between urine glyphosate concentrations (both continuous with categorical) and the risks of developing arthritis, as well as the risks of various types of arthritis. Non-linear correlations have been investigated using restricted cubic spline and smooth curve fitting. We also conducted additional subgroup analyses using categorical defining features.ResultsPatients with arthritis had urine glyphosate levels of 0.4 ng/mL, while non-arthritic individuals had levels of 0.3 ng/mL (p < 0.05). After adjusting for confounding variables, multivariate logistic regression continuous and categorical models demonstrated a significant positive association between elevated urinary glyphosate levels and arthritis risk [1.2 (1.0, 1.4)]. This association was observed in the osteoarthritis (OA) subgroup, with an odds ratio of 1.3 (95% CI: 1.1, 1.6), but was not found in the rheumatoid arthritis (RA) or other arthritis subgroups. Smooth curve fitting and RCS regression analyses further elucidate that urine glyphosate levels exhibit a dose-dependent relationship with the risks of both arthritis and OA, adhering to a linear trend (with a p-value for nonlinearity exceeding 0.05). Subsequent subgroup studies showed that in certain groups of people, the positive relationship between urine glyphosate and arthritis remained significant.ConclusionIncreased exposure to urine glyphosate may be associated with an elevated risk of arthritis, particularly in the subgroup of osteoarthritis.